PENETAPAN KADAR FENOLIK TOTAL EKSTRAK ETANOL DAUN SERUNAI (Chromolaena odorata L.) DENGAN METODE SPEKTROFOTOMETRI UV-Vis - Risa Supriningrum; Henny Nurhasnawati; Siti Faisah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Serunai (Chromolaena odorata L.) is a medicinal plant, including the Asteraceae family. Serunai is used to treat wounds, mouthwash to treat sore throats, coughs, malaria drugs, headache medications, antidiarrheals, antimicrobials, antispasmodics, antihypertensive, anti-inflammatory and diuretic agents. Serunai plants contain chemical compounds tannins, phenols, flavonoids, saponins and steroids. The purpose of this study was to determine the total phenolic content of the leaves of serunai using the UV-Vis spectrophotometric method. The stages of the research include plant determination, sampling, making of simplicia leaf of serunai, making extract by maceration method, phenolic compound test, determination of total phenolic levels by UV-Vis spectrophotometry with Folin-Ciocalteu reagent, comparing gallic acid. The results obtained by an average of total phenolic levels of ethanol extract of serunai is 171.30368 ± 1.9694 mg GAE / g means that in every gram of ethanol extract of flattened leaves is equivalent to 171,30368 mg gallic acid.